Folding and Misfolding of a PDZ Tandem Repeat. Issue 7 (2nd April 2021) - Visconti, Lorenzo; Malagrinò, Francesca; Troilo, Francesca; Pagano, Livia; Toto, Angelo; Gianni, Stefano
Graphical abstract: Highlights: PDZ1 and PDZ2 domain of Whirlin display different thermodynamic stabilities. It is possible to selectively unfold one or both PDZ domains in the P1P2 tandem. A misfolded intermediate accumulates in the folding pathway of P1P2. A quantitative analysis of the folding of P1P2 tandem is provided. Abstract: Although the vast majority of the human proteome is represented by multi-domain proteins, the study of multi-domain folding and misfolding is a relatively poorly explored field. The protein Whirlin is a multi-domain scaffolding protein expressed in the inner ear. It is characterized by the presence of tandem repeats of PDZ domains. The first two PDZ domains of Whirlin (PDZ1 and PDZ2 – namely P1P2) are structurally close and separated by a disordered short linker. We recently described the folding mechanism of the P1P2 tandem. The difference in thermodynamic stability of the two domains allowed us to selectively unfold one or both PDZ domains and to pinpoint the accumulation of a misfolded intermediate, which we demonstrated to retain physiological binding activity. In this work, we provide an extensive characterization of the folding and unfolding of P1P2. Based on the observed data, we describe an integrated kinetic analysis that satisfactorily fits the experiments and provides a valuable model to interpret multi-domain folding. The experimental and analytical approaches described in this study may be of general interest for the interpretation of complex multi-domain protein folding kinetics.